2011
DOI: 10.1080/02699931.2010.547564
|View full text |Cite
|
Sign up to set email alerts
|

The role of disgust propensity in blood-injection-injury phobia: Comparisons between Asian Americans and Caucasian Americans

Abstract: There is a growing body of evidence suggesting the potential role of disgust propensity in blood-injection-injury (BII) phobia. The current study examined associations between disgust propensity and BII phobia symptom severity in Caucasian Americans (n=310) and Asian Americans (n=223). Asian Americans typically scored higher than Caucasian Americans on the BII and disgust measures. The present study also examined the structural relations between gender, cultural background, disgust propensity, and BII phobia s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Kleinknecht et al (1997) found differential disgust-BII model fit between males and females for an American student sample. However, Hirai and Vernon (2011) found that an Asian American sample showed no gender differences on animal disgust, contamination disgust, and BII phobia dimensions. Culture and acculturation levels need to be taken into account to understand gender effects in models of disgust propensity and BII fear.…”
Section: Individualsmentioning
confidence: 80%
See 2 more Smart Citations
“…Kleinknecht et al (1997) found differential disgust-BII model fit between males and females for an American student sample. However, Hirai and Vernon (2011) found that an Asian American sample showed no gender differences on animal disgust, contamination disgust, and BII phobia dimensions. Culture and acculturation levels need to be taken into account to understand gender effects in models of disgust propensity and BII fear.…”
Section: Individualsmentioning
confidence: 80%
“…With US and Dutch samples, Sawchuk et al (2006) reported differential relationships between specific disgust domains and contamination fear, whereas Olatunji et al (2006) reported a model of disgust and BII fear that fit for both samples. Hirai and Vernon (2011) reported gender and cultural differences on levels of BII fear and disgust propensity. The role of disgust propensity in BII fear among Latinos is unknown.…”
Section: Individualsmentioning
confidence: 97%
See 1 more Smart Citation
“…A final consideration is differences in disgust by race or ethnicity. Previous work examining differences in disgust component measures finds evidence that African Americans may be more disgust sensitive than European Americans (Haidt e al., 1994) and that Asian Americans may have greater disgust propensity (Hirai and Vernon, 2011). Williams, Abramowitz, and Olatunji, (2012) found no significant differences in disgust sensitivity between African Americans and European Americans; however, African Americans were more concerned about contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found ethnicity and gender differences in emotion (Eid & Diener, 2001;Mesquita & Frijda, 1992). Also, a few ethnicity by gender interactions have been observed, which suggest that ethnic group membership may influence the existence and magnitude of gender differences in emotion (Brody, 1997;Hirai & Vernon, 2011). In light of evidence suggesting that emotion plays a role in many forms of psychopathology (Berenbaum, Raghavan, Le, Vernon, & Gomez, 2003), it seems likely that ethnicity and gender would influence the role of specific emotions within various forms of psychopathology.…”
Section: Introductionmentioning
confidence: 99%